(untitled) (Scientific journal of the Fergana State University, 2025)
The article is devoted to the development of a general linguistic theory and classification of linguoculturemes, in which the author attempts to develop meta-concepts and meta-terms denoting multilevel types of linguoculturemes, such as phonocultureme, morphocultureme, morphophonocultureme, lexocultureme, syntaxocultureme (represented by phrasecultureme, sentencocultureme), proverbocultureme, textocultureme and paracultureme within only one language (termed “intralinguoculturemes”) or more than one language (termed “interlinguoculturemes”).